Teaching Social Sciences: forming creative, critical and coperative students - Ocaña Fernández, Yolvi (2014)
The main purpose of this article is to understand the importance of Social Sciences as a base for an integral and transforming education in our society. First of all, we will provide a clear and relevant definition of Social Sciences; the basic principle of its unity is strengthened in the variety of knowledge and scientific background. In the second part we mention the value of Social Sciences contribution to education, beginning with the concept; it is necessary to have a meaningful and transcendental didactic, if we want to fulfill the purposes of the National Curricula Design.